Risk stratification of postoperative cardiopulmonary toxicity after trimodality therapy for esophageal cancer - Kowalchuk, Roman O.; Spears, Grant M.; Morris, Lindsay K.; Owen, Dawn; Yoon, Harry H.; Jethwa, Krishan; Chuong, Michael D.; Ferris, Matthew J.; Haddock, Michael G.; Hallemeier, Christopher L.; Wigle, Dennis; Lin, Steven H.; et al. (Frontiers in Oncology, 2023)
Purpose/Objective: Postoperative toxicity for esophageal cancer impacts patient quality of life and potentially overall survival (OS). We studied whether patient and toxicity parameters post-chemoradiation therapy predict for post-surgical cardiopulmonary total toxicity burden (CPTTB) and whether CPTTB was associated with short and long-term outcomes. Materials/Methods: Patients had biopsy-proven esophageal cancer treated with neoadjuvant chemoradiation and esophagectomy. CPTTB was derived from total perioperative toxicity burden (Lin et al. JCO 2020). To develop a CPTTB risk score predictive for major CPTTB, recursive partitioning analysis was used. Results: From 3 institutions, 571 patients were included. Patients were treated with 3D (37%), IMRT (44%), and proton therapy (19%). 61 patients had major CPTTB (score ≥ 70). Increasing CPTTB was predictive of decreased OS (p<0.001), lengthier post-esophagectomy length of stay (LOS, p<0.001), and death or readmission within 60 days of surgery (DR60, p<0.001). Major CPTTB was also predictive of decreased OS (hazard ratio = 1.70, 95% confidence interval: 1.17-2.47, p=0.005). The RPA-based risk score included: age ≥ 65, grade ≥ 2 nausea or esophagitis attributed to chemoradiation, and grade ≥ 3 hematologic toxicity attributed to chemoradiation. Patients treated with 3D radiotherapy had inferior OS (p=0.010) and increased major CPTTB (18.5% vs. 6.1%, p<0.001). Conclusion: CPTTB predicts for OS, LOS, and DR60. Patients with 3D radiotherapy or age ≥ 65 years and chemoradiation toxicity are at highest risk for major CPTTB, predicting for higher short and long-term morbidity and mortality. Strategies to optimize medical management and reduce toxicity from chemoradiation should be strongly considered.